Analisis Kualitas Pohon di 5 Jalur Hijau Kota Pematangsiantar - Annie N Hutagalung; Delvian Delvian; Deni Elfiati (Peronema Forestry Science Journal, 2016)
This study aims to determine the tree species and tree quality found on five green belt in Pematangsiantar. This study was carried out along the Medan road, Sisingamangaraja road, Rakutta sembiring road, Ahmad yani road and D. I Panjaitan road. This research used census and scoring methods. Assessment conducted of tree health involved trunk health and crown health,and then the technical of trees involved threat to buildings, threats to roads, sidewalks and drainage, and threats to electric and telephone wires. Results showed that tree species found in five green belt as much as nine trees. The trees most often found are mahogany (Swietenia mahogani). The quality of trees in five green belt when viewed from the tree health included in light category, and from technical trees included in moderate category. The most good quality tree located on Ahmad yani street, while the most low quality trees are on the Rakutta sembiring street. This is indicated from the cumulative value ≥2,5 on Rakutta sembiring road has the highest percentage that is 14,93 %.Keywords : Green belt, Tree species, Tree quality